Visual Basic 2010 unleashed - Del Sole, Alessandro (Unleashed., 2010)
Foreword by Beth Massi Senior Program Manager, Microsoft Visual Studio Visual Basic 2010 Unleashed is the most comprehensive, practical reference to modern object-oriented programming with Visual Basic 2010. Written by Visual Basic MVP Alessandro Del Sole, a long-time leader of the global VB community, this book illuminates the core of the VB language and demonstrates its effective use in a wide variety of programming scenarios. Del Sole covers both Visual Basic 2010 Professional Edition for professional developers and the Express Edition for hobbyists, novices, and students. Writing for VB programmers at all levels of experience, he walks through using VB 2010 for data access, user interface development, networking, communication, and many other tasks. For those moving from structured languages-including VB 6-he offers detailed guidance on building effective object-oriented code. He also demonstrates how to make the most of Microsoft's underlying .NET platform to write more robust and powerful software. This book's broad coverage includes advanced features such as generics and collections; a thorough introduction to the Visual Studio 2010 IDE and Visual Studio Team System; a full section on data access with ADO.NET and LINQ; practical overviews of WPF and WCF; coverage of web and cloud development with Silverlight and Azure; and advanced topics such as multithreading, testing, and deployment. Understand the Visual Studio 2010 IDE, .NET Framework 4.0, and the anatomy of a VB 2010 application Debug VB applications and implement error handling and exceptions Build efficient object-oriented software with classes, objects, namespaces, and inheritance Work with advanced object-oriented features, including interfaces, generics, delegates, events, and collections Organize, create, and improve classes with the Visual Studio Class Designer Access data with LINQ-including LINQ to Objects, SQL, DataSets, Entities, XML, and Parallel LINQ Build modern Windows applications with WPF controls, brushes, styles, and templates Develop web-centric applications using ASP.NET, Silverlight, and Windows Azure Services cloud computing Create and consume WCF services and WCF Data Services Use advanced .NET 4.0 platform capabilities, including assemblies, multithreading, parallel programming, P/Invoke, and COM interoperability Perform advanced compilations with MSBuild Localize and globalize VB 2010 client applications Alessandro Del Sole, Microsoft MVP for Visual Basic ...